Accumulation of beryllium dust in ITER diagnostic ports after off-normal events. (August 2019) - Vignitchouk, L.; Ratynskaia, S.; Tolias, P.; Pitts, R.A.; De Temmerman, G.; Lehnen, M.; Kiramov, D.
Highlights: The transport and re-solidification of beryllium droplets in ITER were simulated. Diagnostic ports can act as a sink for approximately 10% of the solid dust mass. The global dust deposition pattern in the vessel is unaffected by diagnostic ports. In-vessel dust size distributions can be inferred from dust samples collected locally. Abstract: Dust transport simulations are used to predict the effect of diagnostic ports on the in-vessel inventory of solid beryllium particles produced during mitigated disruptions in ITER. Beryllium dust is assumed to originate from the re-solidification of liquid droplets, which are initially ejected during transient first-wall melting events and subsequently interact with the disrupting plasma. The trajectories of droplets launched with various initial conditions, as well as the time evolution of their temperature and mass, are simulated until either complete vaporization or immobilization upon undergoing a sticking or splashing impact with the wall is realized. The results indicate that approximately 10% of the dust mass in the vessel can be expected to reside inside ports, in particular those located in the equatorial plane or in the lower outboard first wall.